Dental intervention for the irradiated patient: time to re-evaluate dental treatment algorithms?. Issue 6 (July 2020) - Rosen, E.B.; Ahmed, Z.U.; Randazzo, J.D.; Yom, S.; Estilo, C.L.; Huryn, J.M.
Abstract: Modern radiotherapy delivery systems and treatment strategies are aimed at limiting the irradiation of healthy structures in the head and neck. This seeks to mitigate post-treatment toxicities and complications such as osteoradionecrosis of the jaw. Given the changes to radiotherapy, conventional workflows for the management of patients requiring dentoalveolar surgery may no longer be suitable. It may therefore be appropriate to revisit current treatment algorithms for the management of patients with radiotherapy to the jaws who require dentoalveolar surgery. At present, there are poor data on this. Development of a randomised trial may be warranted to establish the true relative risk for extraction of teeth in the setting of modern radiation therapy delivery systems.